Platform evaluation for rapid genotyping of CYP2C9 and VKORC1 alleles. (July 2009) - Joshi, Victoria A; Duffy, Elizabeth; Funke, Birgit H; Farwell, Lisa M; Mancini-Dinardo, Debora; Kucherlapati, Raju
Aims: Warfarin is a commonly prescribed drug with a narrow therapeutic index. Adverse drug reactions owing to over- or under-dosing are common. It is now established that genetic differences between individuals play a major role in warfarin metabolism. In particular, common variants in CYP2C9 ( *2 and *3 ) and VKORC1 (-1639G>A) have been associated with a reduced drug-dosage requirement.Materials & methods: We have evaluated the performance of five platforms that can be used to genotype individuals for these variants. These include Third Wave Technologies Invader ®®, Applied Biosystems TaqMan ®®, AutoGenomics INFINITI™™ 2C9-VKORC1 assay, Osmetech eSensor ®® XT-8 warfarin sensitivity test and the Idaho Technologies LightScanner ®® .Results & conclusions: Excluding failures, all of these technologies had 100% concordance rates with either Sanger sequencing or another validated technology. All of these platforms had high sensitivity and specificity and are therefore appropriate for clinical molecular diagnostics. Therefore, platform choice is likely to be driven by clinical laboratories interested in performing this service taking other factors into account, including turnaround time, capacity, cost and ease of use.